Performance of the Biomark HD real-time qPCR System (Fluidigm) for the detection of nasopharyngeal bacterial pathogens and Streptococcus pneumoniae typing - Olwagen, Courtney P.; Adrian, Peter V.; Madhi, Shabir A. (Nature Research, 2019)
Traditional qPCR assays for pneumococcal detection and serotype characterization require large sample volume, is expensive and labor intensive. We aimed to develop a quantitative nanofuidic Fluidigm assay to overcome some of these shortcomings. A quantitative Fluidigm assay was established to detect 11 bacterial pathogens, 55 pneumococcal serotypes and 6 serotypes of H. infuenzae. The Fluidigm assay results were compared to conventional qPCR and culture. All reactions in the Fluidigm assay efectively amplifed their respective targets with high sensitivity and specifcity compared to qPCR. There was excellent concordance between qPCR and Fluidigm for detection of carriage prevalence (kappa>0.75) and density (Rho>0.95). Fluidigm identifed an additional 7 (4.2%) serotypes over those detected by qPCR. There was a modest concordance between culture and Fluidigm for the majority of reactions detecting S. pneumoniae serotypes/serogroups (kappa>0.6), with Fluidigm identifying an additional 113 (39.1%) serotypes. Discordant results between the three methods were associated with a low carriage density. The Fluidigm assay was able to detect common pneumococcal serotypes, H. infuenzae serotypes, and other common nasopharyngeal bacterial organisms simultaneously. Deployment of this assay in epidemiological studies could provide better insight into the efect of PCV immunization on the nasopharyngeal microbiota in the community
Keywords: Biological sciences; Infectious-disease diagnostics; Nasopharyngeal bacterial pathogens; Streptococcus pneumoniae; SDG-17: Partnerships for the goals